Assessing the Influence of Peer Collaboration, Classroom Management, and Assessment Practices on Student Motivation in Secondary Education - Amri, Miftachul; Prasetyo, Joko; Halim, Chandra; Adhimas, Yogi Bagus (International Journal of Business, Law, and Education, 2024)
This research investigates the influence of peer collaboration, classroom management practices, and assessment strategies on student motivation in educational settings. The study utilizes a mixed-methods approach, combining quantitative surveys, observations, and qualitative interviews to gather comprehensive data. Results from correlation and regression analyses reveal significant positive correlations between student motivation and peer collaboration experiences, classroom management perceptions, and effective assessment practices. Thematic analysis of qualitative data further elucidates key themes related to peer collaboration dynamics, classroom management strategies, assessment practices, and student motivation factors. Integration of quantitative and qualitative findings emphasizes the interconnectedness of these factors and their collective impact on student engagement and learning outcomes. The study concludes with actionable recommendations for educators and policymakers to optimize teaching practices, create supportive learning environments, and enhance student motivation.